Application of pulse power supply for diamond coatings deposition in glow discharge plasma - Koshevoy, K.I.; Volkov, Yu.Ya.; Strel’nitskij, V.E.; Reshetnyak, E.N. (Вопросы атомной науки и техники, 2019)
Comparative studies of diamond coatings deposition have been carried out in the glow discharge plasma stabilized by a magnetic field in methane-hydrogen medium with using the DC or pulse power supply. It was shown that using of a pulsed power supply leads to an increase of the input power range at which the discharge is stable in comparison with DC one. In addition a significant increase of the samples temperature and the diamond coating growth rate were achieved at the same average power introduced into the discharge. The resulting diamond coating was of high quality and purity. Були проведені порівняльні дослідження по застосуванню як імпульсного, так і постійного джерел струму для осадження алмазних покриттів у плазмі тліючого розряду, стабілізованого магнітним полем у метановодневому середовищі. Показано, що використання імпульсного джерела живлення призводить до збільшення діапазону вхідної потужності, при якій розряд стійкий в порівнянні з розрядом постійного струму. Крім того, при тій же середній потужності, що вводиться в розряд, досягається значне збільшення температури зразків і швидкості росту алмазного покриття. Отримане алмазне покриття відрізняється високою якістю і чистотою. Были проведены сравнительные исследования по применению как импульсного, так и постоянного источников тока для осаждения алмазных покрытий в плазме тлеющего разряда, стабилизированного магнитным полем в метановодородной среде. Показано, что использование импульсного источника питания приводит к увеличению диапазона входной мощности, при которой разряд устойчив по сравнению с разрядом постоянного тока. Кроме того, при той же средней мощности, вводимой в разряд, достигается значительное увеличение температуры образцов и скорости роста алмазного покрытия. Полученное алмазное покрытие отличается высоким качеством и чистотой.